Pengembangan Perangkat Pembelajaran Matematika untuk SMP Kelas VII Semester Genap dengan Pendekatan Saintifik - Bayu Prasetyo; Rusgianto Heri Santosa (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2015)
Tujuan penelitian ini adalah menghasilkan produk berupa perangkat pembelajaran matematika untuk SMP kelas VII semester genap dengan pendekatan saintifik yang meliputi RPP, LKS, dan instrumen penilaian hasil belajar siswa yang valid, praktis, dan efektif. Model pengembangan yang digunakan dalam penelitian ini adalah model pengembangan Four-D yang meliputi empat tahap yaitu: (1) pendefinisian, (2) perancangan, (3) pengembangan, dan (4) penyebaran. Tidak semua produk dilakukan uji pengembangan. Uji pengembangan produk hanya dilakukan pada materi persamaan dan pertidaksamaan linear satu vaiabel. Hasil penelitian menunjukkan bahwa produk yang telah dilakukan uji pengembangan memenuhi kriteria valid, praktis, dan efektif. Produk memenuhi kriteria valid berdasarkan persentase penilaian ahli mencapai 100%. Produk memenuhi kriteria praktis berdasarkan penilaian guru dan siswa yang termasuk dalam kategori sangat baik, serta berdasarkan hasil observasi keterlaksaan pembelajaran. Produk memenuhi kriteria efektif berdasarkan hasil belajar siswa pada kompetensi sikap, pengetahuan, dan keterampilan. Persentase siswa yang mencapai KKM untuk kompetensi sikap, pengetahuan, dan keterampilan melebihi 75%.Kata Kunci: pengembangan, perangkat pembelajaran, pendekatan saintifik Developing Mathematics Instructional Materials for 7th Grade Students of Junior High School in Second Semester Based on the Scientific Approach AbstractThe aim of this study is to produce mathematics instructional materials for 7th grade students of junior high school in their second semester based on the scientific approach including lesson plans, student’s worksheets, and assessment instrument of learning achievement that fulfill the quality criteria of validity, practicality, and effectiveness. This research was a development study using the Four-D development model with four steps: (1) define, (2) design, (3) develop, and (4) disseminate. Development test was not done for all products. Development testing of product was done only for linear equality and inequality with one variable. The result of the study shows that the product which has done development test is valid, practical, and effective. The product fulfills the validity criterion. It is shown by the percentage of experts’ appraisal which reaches 100% that belongs to a valid category. The product fulfills the practicality criterion based on teacher and student assesment to the instructional material that is in a very good category. The product also fulfills the practicality criterion based on the percentage of teaching implementation. The percentage of teaching implementation exceeded 90%. The product fulfills the effectiveness criterion based on student learning achievement in attitude, knowledge, and skill competency. The percentage of students that achieve minimum mastery criteria for attitude, knowledge, and skill competency exceeded 75%.Keywords: development, instructional material, scientific approach